Karyawan Alfamart Kinibalu Kota Palangka Raya sebagai Cheerful Robots - Silalahi, Juli Natalia (Prodi Sosiologi Agama, 2020)
The purpose of this study is to explain the meaning of work rationality for Alfamart employees (Crew, ACOS, COS) while serving at PT. Sumber Alfaria Tri Jaya, TBK (Alfamart). The benefits of research are criticizing the workings of capitalism in the objective reality of Alfamart employees. Meaning was analyzed using the perspective of C. Wright Mills about Cheerful Robots. Rationality in Mills's perspective that ratio work must precede objective reality, because objective reality is the exploitation of the human ratio. The present social reality is not the work of ratio work, but the work of technology. Accordingly, Alfamart employees understand their work as technological work, not ratio work. lfamart makes the reproduction of excited robots that are workers who are ready to run Standard Operating Procedures (SOP) from PT. Sumber Alfaria Tri Jaya, TBK. The method used is qualitative research with a qualitative descriptive approach. The results of this study indicate: 1. Alfamart employees do not have the creative power to speak out about the discomfort they get, because all of that is covered with sweet promises from the company. Though the promise is not certain, and the income obtained by Alfamart employees is very far from the owner of PT. Sumber Alfaria Trijaya and structural position holders (Korwil, Inventory Collection/IC, Directors, President Commissioners, etc.). 2. Without realizing by this Alfamart employee that they become Cheerful Robots that are driven by PT. Sumber Alfaria Tri Yaya, Tbk. They consider this work to be fine, even though they know there is a loss they are getting, but it is considered fairness and responsibility. They lose their reason and autonomy of mind.